Preparing orphaned/unaccompanied children for sustainable livelihood through "home"-based entrepreneurial education : implications from a care service provider in northern Thailand - Nga, Ao Ieong Si (2019)
Entrepreneurship education has been widely discussed in the realm of general education system, but little research has targeted orphaned/unaccompanied children. This research paper explores how entrepreneurship education can be implemented on orphaned/unaccompanied children, and what challenges may occur during the process from educational leaders’ perspective. This research approaches the topic with Sustainable Livelihood Framework. Qualitative case study and semi-structured interview were conducted with a director from a care service provider in northern Thailand. The findings inform us several feasible ways to implement entrepreneurship education on orphaned/unaccompanied children: 1) opting for an (emulated) “family” business approach, 2) constructing a safety net for risk taking, 3) prioritizing local leadership, 4) adopting short supply chain businesses, 5) holding a flexible, responsive, lenient attitude. In terms of challenges in practice, the director reported fixed mind-set of the local people and their apprehensive attitudes towards innovation and risk-taking were the main challenges. This research does not intend to dish out a one-size-fit-all solution because the education is highly dependent on the staff, the people in charge and the people involved in the work. Nevertheless, the education approach fits into the educational paradigm of constructivism because the approach is experience-driven. Practitioners from relevant fields may draw insight from this context where they see fit. Future research may explore other ways of constructing safety nets for risk-taking and innovation with methods that are less material-dependent.